(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article discusses the essence, purpose of HR analytics, and the main tasks in personnel management that can be performed with its help, the main advantages of implementing HR analytics in organizations. The article also reveals the main prospects and problems of implementing HR analytics in Russia. An approximate description of the basic competencies that specialists in the field of HR analytics should have is given. The article also gives an example of the most common metrics that are used in HR analytics.